The influence of governance structure on sustainability disclosure: empirical evidence from federal statutory bodies / Redvin Bilu, Asmah Abdul Aziz and Faizah Darus - Bilu, Redvin; Abdul Aziz, Asmah; Darus, Faizah (Universiti Teknologi MARA Cawangan Selangor, 2016)
The federal statutory bodies which were established to support and deliver the Federal Government objectives have the responsibility to ensure that their policies and activities are aligned with that of the government sustainable development agenda. The aim of this study is to examine the influence of board characteristics, namely the board size, women directors on board, and board designation on sustainability information disclosure by the federal statutory bodies in Malaysia. The release of sustainability information by federal statutory bodies provides an indication of their commitment towards sustainability issues. A sustainability disclosure index was used to examine 112 Malaysian federal statutory bodies’ websites for the year 2015. The agency theory was used to explain the relationships of the variables in this study. The overall results from the study revealed that the extent of sustainability information disclosed by Malaysian federal statutory bodies was still low. The results of the multiple regression analysis revealed that board designation had a significant positive influence on the disclosure of sustainability information by federal statutory bodies in Malaysia, suggesting that influential and reputable board members can put pressure on the management of federal statutory bodies to reveal their sustainability information to the public.